New Hybrid Compounds Combining Fragments of Usnic Acid and Monoterpenoids for Effective Tyrosyl-DNA Phosphodiesterase 1 Inhibition - Nadezhda S. Dyrkheeva (Biomolecules, 2021)
Usnic acid (UA) is a secondary metabolite of lichens that exhibits a wide range of biological activities. Previously, we found that UA derivatives are effective inhibitors of tyrosyl-DNA phosphodiesterase 1 (TDP1). It can remove covalent complex DNA-topoisomerase 1 (TOP1) stabilized by the TOP1 inhibitor topotecan, neutralizing the effect of the drugs. TDP1 removes damage at the 3′ end of DNA caused by other anticancer agents. Thus, TDP1 is a promising therapeutic target for the development of drug combinations with topotecan, as well as other drugs for cancer treatment. Ten new UA enamino derivatives with variation in the terpene fragment and substituent of the UA backbone were synthesized and tested as TDP1 inhibitors. Four compounds, 11a-d, had IC50 values in the 0.23–0.40 μM range. Molecular modelling showed that 11a-d, with relatively short aliphatic chains, fit to the important binding domains. The intrinsic cytotoxicity of 11a-d was tested on two human cell lines. The compounds had low cytotoxicity with CC50 ≥ 60 μM for both cell lines. 11a and 11c had high inhibition efficacy and low cytotoxicity, and they enhanced topotecan’s cytotoxicity in cancerous HeLa cells but reduced it in the non-cancerous HEK293A cells. This “protective” effect from topotecan on non-cancerous cells requires further investigation.